How to design a successful microarray experiment - Breitling, Rainer (Henry Stewart Talks, 2009)
Why do microarray experiments?, Criteria of success, Number of arrays and replicates, Statistics for small datasets, Sample quality and effect sizes, Which controls to use, Pooling and batch effects, Array platform differences
Reviewed at 2022/04/12